Opioid receptor activation suppresses the neuroinflammatory response by promoting microglial M2 polarization - Mali, Akash S; Novotny, Jiri (Molecular and cellular neurosciences, 2022)
Activation of microglia is considered the most important component of neuroinflammation. Microglia can adopt a pro-inflammatory (M1) or anti-inflammatory (M2) phenotype. Opioid receptors (ORs) have been shown to control neurotransmission of various peptidergic neurons, but their potential role in regulating microglial function is largely unknown. Here, we aimed to investigate the effect of the OR agonists DAMGO, DADLE and U-50488 on the polarization of C8-B4 microglial cells. We observed that opioids suppressed lipopolysaccharide (LPS)-triggered M1 polarization and promoted M2 polarization. This was reflected in lower phagocytic activity, lower production of NO, lower expression of TNF-α, IL-1β, IL-6, IL-86 and IL-12 beta p40 together with higher migration rate, and increased expression of IL-4, IL-10, arginase 1 and CD 206 in microglia, compared to cells affected by LPS. We demonstrated that the effect of opioids on microglial polarization is mediated by the TREM2/NF-κB signaling pathway. These results provide new insights into the anti-inflammatory and neuroprotective effects of opioids and highlight their potential in combating neurodegenerative diseases.
Keywords: Receptors, Opioid; antiflogistika; Inflammation; lidé; zánět; opioidní analgetika; lipopolysacharidy; Analgesics, Opioid; Microglia; mikroglie; Anti-Inflammatory Agents; receptory opiátové; Lipopolysaccharides; Humans